Performance Traits and Milk Composition of Different Cattle Breeds Reared under Subtropical Conditions of Khyber Pakhtunkhwa Pakistan (Journal of Agriculture and Veterinary Science, 2025)
The present study was conducted to investigate the comparative adaptability of different exotic cattle breeds in subtropical conditions. For these purposes, the performance characteristics of three different cattle breeds, including Holstein Friesian (HF), Australian Friesian (AF), and Jersey, reared at Livestock Research & Breeding Farm, The University of Agriculture, Peshawar, were studied. Data from 2010 to 2020 were utilized. Results showed that a significantly higher daily milk yield (DMY), peak milk yield (PMY), and lactation yield (LY) were recorded for the HF breed than for AF and Jersey. The significantly highest DMY, PMY, and LY were recorded in the fifth parity. A significantly higher fat content was found in the milk of the Jersey breed as compared to HF and AF breeds. Protein and solid non-fat (SNF) were significantly higher in the HF breed than in the AF and Jersey breeds. The DMY and the SMY were significantly correlated with PMY, but a negative, insignificant Pearson correlation was found between Lactose, Total Solids, and pH; however, protein and SNF showed a positive Pearson correlation. The highest production performance was observed in the HF breed, indicating its better productive performance under the prevailing management and climatic conditions. Therefore, the HF breed of cattle should be raised for future breeding, according to the study’s current findings.